2008
DOI: 10.1097/01.anc.0000324341.24841.6e
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Noise in the Neonatal Intensive Care Unit Ambient Levels and Perceptions of Contributing Factors

Abstract: Elevated sound levels need to be addressed in individual NICUs around the country. Further exploratory studies, as well as research regarding effective methods of decreasing sound levels in the NICU environment, are necessary. NICUs can implement behavioral and structural changes that can decrease the sound levels in the NICU environment and decrease the potential for exposure of patients to the harmful physiological effects of increased sound levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 23 publications
3
71
0
2
Order By: Relevance
“…Studies have found evidence for high levels of sound pressure in NICU and inside the incubators (6,8,13) and have indicated the deleterious eff ects on the health of neonates, health care professional and family, although there is s ll a scarcity of studies in the Brazilian and interna onal Nursing literature on the subject here researched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found evidence for high levels of sound pressure in NICU and inside the incubators (6,8,13) and have indicated the deleterious eff ects on the health of neonates, health care professional and family, although there is s ll a scarcity of studies in the Brazilian and interna onal Nursing literature on the subject here researched.…”
Section: Discussionmentioning
confidence: 99%
“…Loud noise causes psycho-biological eff ects in the new-born, with altera ons in the sleep cycle and wakefulness, immediate changes in vital signs, and inadequate growth and development (13) . This is in addi on to the fact that sleep disturbance in the neonate can lead to impaired immune function, decreased inspiratory muscle endurance, diffi culty in weaning from mechanical ventilation, a possible association with delirium and severe morbidity and impaired secretion of melatonin, the key circadian regulatory hormone (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In such a nurturing and confined environment, they achieve proper neurosensory development. (1) In contrast, the premature infant, prior to 37 weeks of gestational age, spends their first months in the Neonatal Intensive Care Unit (NICU) environment, which is often a harsh, invasive and noisy environment at a time of physiological limitation and central nervous system immaturity, making them especially vulnerable to NICU environmental stress that can often continue. (2) They also have an increased need for long term intensive care, which makes them more sensitive to the negative effects of the NICU.…”
Section: Introductionmentioning
confidence: 99%
“…(2) They also have an increased need for long term intensive care, which makes them more sensitive to the negative effects of the NICU. (1) According to its definition, noise is undesirable sound and sound is vibration in a medium, usually air. When these vibrations occur at high levels sound may become harmful.…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to excessive noise, the newborn body can present different responses, such as: hypoxia, release of adrenocorticotropic hormone and adrenaline in the blood stream, increase in heart rate, systemic vasoconstriction, , pupil dilation, increase in blood and intracranial pressure, increase in oxygen consumption and caloric requirements, that can lead to delay in weight gain in the long term. The noise can lead to changes in infants' states of sleep and wakefulness, making them annoyed and whining, hindering their development (3)(4)(8)(9) . Additionally, the excessively noise environment affects infants' ability to interact and can change their behavioral state, leading to "fading" and, thus, affecting in some way the bond between parents and the infant (5) .…”
Section: Introductionmentioning
confidence: 99%